Kinerja Kode Rapid Tornado Dengan Reed-Solomon Precode - Valentino Pradnya Mahinda; Jonathan Aristo; Lydia Sari (Fakultas Teknik, Universitas Katolik Widya Mandala Surabaya, 2016)
Rapid Tornado code is constructed from a Luby Transform code concatenated with a precode. This code is used to protect data sent over an erasure channel. An erasure channel will typically corrupt a number of transmitted data, causing the loss of several information symbols. Despite this loss, the transmitted data can still be reconstructed by the receiver if Rapid Tornado or Luby Transform code is used. In this paper, an encoding and decoding process using Rapid Tornado and Reed-Solomon precode is simulated with 9 information symbols sent over an erasure channel. The simulation result is compared to that of a Luby Transform code. It is shown that Rapid Tornado enables the reconstruction of data despite the loss of codewords transmitted over an erasure channel. Kata kunci : Binary Erasure Channel, Rapid Tornado, Luby Transform, degree distribution